Social War Losses - Žunec, Ozren (2003)
Author examines the impact of war on society as an institution. The material damages and human losses caused by war present only one fraction of the overall loss a society suffers, albeit most visible. The more profound impact can be seen in decomposition and rapid change of social values that contribute to the long-term feeling of insecurity of the members of the scociety. Social change caused by war runs deeper and brings into question the very fundament of the society. The theoretical insights are illustrated by the post-war developments in the countries affected by war in former Yugoslavia.
Projekt MZOS
ENG